Fast converging with high accuracy estimates of satellite attitude and orbit based on magnetometer augmented with gyro, star sensor and GPS via extended Kalman filter - Tamer Mekky Ahmed Habib (Egyptian Journal of Remote Sensing and Space Sciences, 2011)
The primary goal of this work is to extend the work done in, Tamer (2009), to provide high accuracy satellite attitude and orbit estimates needed for imaging purposes and also before execution of spacecraft orbital maneuvers for the next Egyptian scientific satellite. The problem of coarse satellite attitude and orbit estimation based on magnetometer measurements has been treated in the literature. The current research expands the field of application from coarse and slow converging estimates to accurate and fast converging attitude and orbit estimates within 0.1°, and 10 m for attitude angles and spacecraft location respectively (1-σ). The magnetometer is used for both spacecraft attitude and orbit estimation, aided with gyro to provide angular velocity measurements, star sensor to provide attitude quaternion, and GPS receiver to provide spacecraft location. The spacecraft under consideration is subject to solar radiation pressure forces and moments, aerodynamics forces and moments, earth’s oblateness till the fourth order (i.e. J4), gravity gradient moments, and residual magnetic dipole moments. The estimation algorithm developed is powerful enough to converge quickly (actually within 10 s) despite very large initial estimation errors with sufficiently high accuracy estimates.